2010
DOI: 10.1073/pnas.1000087107
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete recovery and individualized responses of the human distal gut microbiota to repeated antibiotic perturbation

Abstract: The indigenous human microbiota is essential to the health of the host. Although the microbiota can be affected by many features of modern life, we know little about its responses to disturbance, especially repeated disturbances, and how these changes compare with baseline temporal variation. We examined the distal gut microbiota of three individuals over 10 mo that spanned two courses of the antibiotic ciprofloxacin, analyzing more than 1.7 million bacterial 16S rRNA hypervariable region sequences from 52 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

94
1,677
9
28

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,007 publications
(1,808 citation statements)
references
References 37 publications
94
1,677
9
28
Order By: Relevance
“…32 , 33 Unfortunately, it is also a major disruptor of the gut microbiota, and has been shown to profoundly alter the natural taxa in the GIT after only a single course of treatment, with some taxa never recolonizing. 34 Our studies provide further support of this indirect action of the antibiotic, as it led to a 1 log-reduction of the representative SI consortia in this study. In contrast, the phage preparation only impacted the E. coli populations, and had no impact on any of the other six “commensal” bacterial species included in our model.…”
Section: Discussionsupporting
confidence: 80%
“…32 , 33 Unfortunately, it is also a major disruptor of the gut microbiota, and has been shown to profoundly alter the natural taxa in the GIT after only a single course of treatment, with some taxa never recolonizing. 34 Our studies provide further support of this indirect action of the antibiotic, as it led to a 1 log-reduction of the representative SI consortia in this study. In contrast, the phage preparation only impacted the E. coli populations, and had no impact on any of the other six “commensal” bacterial species included in our model.…”
Section: Discussionsupporting
confidence: 80%
“…Many antibiotic effects are more subtle (as shown in another study with Finnish children, Yassour et al ., 2016), vary from chemical class to chemical class of antibiotics and from individual to individual, and reflect preceding antibiotic treatments. A study by Dethlefsen and Relman (2011) illustrates the situation. Three adults who each experienced two courses of treatment with ciprofloxacin were followed with 50 samples over 10 months.…”
Section: Eliminating Undesired Bacteria From the Gut Microbiomementioning
confidence: 99%
“…The weight gain effects from antibiotics observed in animals have been suggested to also potentially occur in humans. For instance, the different groups of bacteria which have been affected after antibiotic consumption may take several months to recover (Jernberg et al 2010;Dethlefsen and Relman 2011). Therefore, it has been suggested that antibiotic therapy (at therapeutic doses) in early life can dramatically affect the evolution of infant gut microbiota (Fouhy et al 2012), making these treated children prone to develop obesity, due to a dysbiosis of their gut microbiota.…”
Section: Strategies To Manipulate Gut Microbiota In Obesity Antibioticsmentioning
confidence: 99%